Analisis Pengembangan Budidaya Porang di Desa Batu Rotok Kecamatan Batulanteh Kabupaten Sumbawa - Siti Nurwahidah; Nila Wijayanti; Desi Rahmayanti (AGRIFITIA : Journal of Agribusiness Plantation, 2022)
Porang plant is a non-wood forest products (NTFPs) in the form of tuber producing starch that has many uses. In Batu Lanteh District, Sumbawa Besar NTB porang plant  grow at privately owned forests and state forest , but so far has not been well developed. Therefore, this study was done in order to get information about internal and external factors that affecting porang plant development and to get development strategy of porang plant.This study was conducted in the village of Batu Rotok, Batu Lanteh District, Sumbawa Besar NTB. This location was chosen because of some factors such as many porang farmers, appropriate land for planting porang, and many farmers who cultivate porang. This study aims to identify the internal and external factors in cultivating porang plant as an effort to improve the income of the society in Bato Rotok Village. The sample is taken through Purposive sampling.  Purposive sampling is the character of the sample members taken from a deep consideration which is considered or believed by the researcher to represent the character of the population. The sample of this study is 19 samples namely  13 farmers, 2 porang sellers , 1 sample from KPH Batu Lanteh, 3 samples from government related agency. Analisis SWOT is used to analyze the data in this study. There are some internal and external strategies to develop porang cultivation as a way to increase income of the society in Batu Rotok village, Batu Lanteh district  namely: 1.  Internal factors; Strengths: Porang can grow under the shade, it has suitable natural condition, it is easy to cultivate, it doesn’t need intensive maintenance, it is planted once, it contains nutrience especially carbohydrate. Weaknesses: Porang’ initial growth need time, it is not widely known and used by the society, Public knowledge of porang is still limited, and Porang plants cannot be directly consumed. 2. External Factors; Opportunities: porang has high selling value, Export needs of porang are still high, the society has wide land to plant porang, and policy support from the government. Threats: The number of entrepreneurs is still limited, the prices are unstable, Lack of socialization of counseling and assistance, Market information is still difficult (tends to be closed). According to the SWOT matrix, it can be concluded that  developing of Porang plants in the village of Batu Rotok, Batu Lanteh District has the best alternative strategies through the strategy of SO, this strategy uses the strengths to utilize the opportunities. so that, porang farmers can develop porang plant in Batu Rotok village therefore they can get an optimal income.  With alternative strategies as follows: 1). Utilizing suitable natural conditions and easy cultivation process in order to meet export needs which are still high. 2). many benefits and nutritional content of porang plants, if it is followed by the right processing process, it will increase the selling value of porang and it can be used as an alternative food. Key words: Identification, Factor, External, Internal, Porang